154k views
3 votes
Solve for b.
b +3(3 - 2b) = 1 - 2(b + 1)

User Kleinux
by
6.8k points

1 Answer

2 votes

Answer:

b+3(3-2b)=1-2(b+1)

One solution was found :

b = 10/3 = 3.333

Rearrange:

Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation :

b+3*(3-2*b)-(1-2*(b+1))=0

Step by step solution :

Step 1 :

Equation at the end of step 1 :

(b+(3•(3-2b)))-(1-2•(b+1)) = 0

Step 2 :

Equation at the end of step 2 :

(b + 3 • (3 - 2b)) - (-2b - 1) = 0

Step 3 :

Equation at the end of step 3 :

10 - 3b = 0

Step 4 :

Solving a Single Variable Equation :

4.1 Solve : -3b+10 = 0

Subtract 10 from both sides of the equation :

-3b = -10

Multiply both sides of the equation by (-1) : 3b = 10

Divide both sides of the equation by 3:

b = 10/3 = 3.333

One solution was found :

b = 10/3 = 3.333

Explanation:

User Dmitriy Sosunov
by
6.3k points